Shared Decision Making in Health Care: Theoretical Perspectives for Why It Works and For Whom. (August 2022) - Resnicow, Ken; Catley, Delwyn; Goggin, Kathy; Hawley, Sarah; Williams, Geoffrey C.
Applying both theoretical perspectives and empirical evidence, we address 2 key questions regarding shared decision making (SDM): 1) When should SDM be more patient driven, and when should it be more provider driven? and 2) Should health care providers match their SDM style/strategy to patient needs and preferences? Self-determination theory, for example, posits a distinction between autonomy and independence. A patient may autonomously seek their health care provider's input and guidance, perhaps due to low perceived competence, low coping resources, or high emotional arousal. Given their need state, they may autonomously require nonindependence. In this case, it may be more patient centered and need supportive to provide more provider-driven care. We discuss how other patient characteristics such as personality attributes, motivational state, and the course of illness and other parameters such as time available for an encounter may inform optimal provider decision-making style and strategy. We conclude that for some types of patients and clinical circumstances, a more provider-driven approach to decision making may be more practical, ethical, and efficacious. Thus, while all decision making should be patient centered (i.e., it should consider patient needs and preferences), it does not always have to be patient driven. We propose a flexible model of SDM whereby practitioners are encouraged to tailor their decision making behaviors to patient needs, preferences, and other attributes. Studies are needed to test whether matching decision-making behavior based on patient states and traits (i.e., achieving concordance) is more effective than simply providing all patients with the same type of decision making, which could be tested using matching/mismatching designs.